Hubungan Kejadian Melasma terhadap Paparan Sinar Ultraviolet (UV) pada Pekerja Luar Ruangan di Pasar Induk Minasa Maupa - Fadhilah, Andi Sausan; Vitayani, Sri; Namirah, Hanna Aulia; Yuniati, Lisa; Rasfayanah, Rasfayanah (Faculty of Medicine, 2025)
Melasma is a common hyperpigmentation disorder that typically appears on sun-exposed areas of the face and is often associated with Ultraviolet (UV) exposure and hormonal factors. This study aimed to examine the relationship between UV exposure and melasma incidence among outdoor workers at Minasa Maupa Central Market, considering hormonal contraceptive use as a confounding factor. A cross-sectional design was used, involving 32 female respondents selected through purposive sampling. Data were collected via observation and validated questionnaires, then analyzed using univariate and bivariate Chi-Square tests. Results indicated a significant relationship between prolonged UV exposure (?4 hours) and melasma occurrence (p=0.022), as well as between hormonal contraceptive use and melasma (p=0.028). However, no significant interaction was found between UV exposure duration and contraceptive use (p=0.849). These findings highlight that UV exposure and hormonal contraceptive use independently contribute to melasma risk. Skin protection education and medical monitoring for contraceptive users are recommended preventive strategies. Future research using longitudinal design and direct UV intensity measurement is suggested to enhance understanding and accuracy.